2020
DOI: 10.1186/s13102-020-00214-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal time-response window for the use of photobiomodulation therapy combined with static magnetic field (PBMT-sMF) for the improvement of exercise performance and recovery, and for how long the effects last? A randomized, triple-blinded, placebo-controlled trial

Abstract: Background The optimal time-response window for photobiomodulation therapy (PBMT) using low-level laser therapy (LLLT) and/or light emitting diodes therapy (LEDT) combined with static magnetic fields (sMF) before physical activity still was not fully investigated. The aim of the present study was to investigate the better of four time-response windows for PBMT combined with sMF (PBMT-sMF) use before exercise in humans. Methods A pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…In our study, we observed that the use of PBMT-sMF not only increased muscle thickness and muscle strength, [57][58][59] but also prevented atrophy due to disuse, 34 as previously observed in skeletal muscles. In addition, there is evidence that PBMT modulates inflammatory processes by decreasing the CRP levels in skeletal muscles, 60,61 which was also observed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, we observed that the use of PBMT-sMF not only increased muscle thickness and muscle strength, [57][58][59] but also prevented atrophy due to disuse, 34 as previously observed in skeletal muscles. In addition, there is evidence that PBMT modulates inflammatory processes by decreasing the CRP levels in skeletal muscles, 60,61 which was also observed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the direct comparation with other randomized controlled trials is limited. However, we observed that the use of PBMT-sMF increased the muscle thickness and consequently its ability to generate strength, 43-45 and also to prevent the harms due disuse 30 as previously observed in skeletal muscles of humans. In addition, there is evidence that PBMT modulates the inflammatory process through decreased CRP levels also in skeletal muscle of humans, 46,47 as we observed in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Yet, many of these repercussions, as well as the complex clinical applications are still incompletely known. Some positive effects were also obtained by simultaneously applying PBMT and static magnetic fields, which we considered in this review [100][101][102][103].…”
Section: Discussionmentioning
confidence: 99%